Correlation of PD-L1 and HIF-1 Alpha Expression with KRAS Mutation and Clinicopathological Parameters in Non-Small Cell Lung Cancer - Seda Er Özilhan; Safa Can Efil; Doğukan Çanakçı; Yetkin Ağaçkıran; Didem Şener Dede; Nilüfer Onak Kandemir; Mehmet Doğan; Tuba Dilay Kökenek Ünal; Merve Meryem Kıran; Serra Kayaçetin; Hilal Balta; Hayriye Tatlı Doğan (Current Issues in Molecular Biology)
Background: Lung cancer remains the leading cause of cancer-related deaths worldwide, with non-small cell lung carcinomas (NSCLCs) comprising the majority of cases. Among the common driver mutations, KRAS plays a critical role in guiding treatment strategies. This study evaluates the expression of programmed death-ligand 1 (PD-L1) and hypoxia-inducible factor 1-alpha (HIF-1α) in KRAS-mutant NSCLCs and investigates their associations with clinicopathological findings. Methods: A total of 85 cases with KRAS mutations were analyzed. Immunohistochemical staining for HIF-1α and PD-L1 was performed, and their relationships with mutation status and prognostic variables were assessed. Results: A significant correlation was identified between HIF-1α expression and PD-L1 expression in tumor cells. While the KRAS G12C mutation was not significantly associated with HIF-1α expression in tumor cells, it demonstrated a notable relationship with HIF-1α expression in the tumor microenvironment and PD-L1 expression. However, PD-L1 and HIF-1α expression did not significantly influence overall survival outcomes. Conclusions: Expression of PD-L1 was positively correlated with HIF-1α, which may provide evidence for a novel therapy targeting PD-L1 and HIF-1α in NSCLC. Further comprehensive studies are warranted to elucidate the prognostic implications of tumor–microenvironment and mutation interactions.